Factors for strengthening the organizational resilience by the case of organizations providing social services - Gečienė, Jolita; Raišienė, Agota Giedrė (Socialinė teorija, empirija, politika ir praktika, 2019)
The article analyses the factors that influence the organizational resilience of public welfare organizations providing social services. Organizational resilience determines the ability of organizations to adapt and overcome unforeseen changes caused by the external environment. The article distinguishes the theoretical principles of organizational resilience and presents the results of the research, on the basis of which the preconditions for strengthening the resistance of organizations are based, and an empirical model of organizational resilience key factors is proposed.